2013
DOI: 10.1007/s13762-013-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium (II)-selective electrode based on palm shell activated carbon modified with task-specific ionic liquid: kinetics and analytical applications

Abstract: In this study, palm shell activated carbon modified with task-specific ionic liquid was used as a novel electrode component for the potentiometric determination of cadmium ions in water samples. The proposed potentiometric sensor has good operating characteristics, including relatively high selectivity towards the Cd (II) ion, a Nernstian response to Cd (II) ions in a working concentration range of 1.0 9 10 -9 -1.0 9 10 -2 M, with a reasonable detection limit of 1 9 10 -10 M and a slope of 30.90 ± 1.0 mV/decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We have also tested trioctylmethylammonium salicylate (TOMAS), with a similar chemical structure to TOMATS, but bearing an alcohol group instead of a thiol (SH-) group. This IL has shown to be a good extractant for some metals such as Cu(II) and Cd(II) [29], but it can also interact with Hg when incorporated in an electrode designed for the potentiometric determination of Cd(II) [30].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also tested trioctylmethylammonium salicylate (TOMAS), with a similar chemical structure to TOMATS, but bearing an alcohol group instead of a thiol (SH-) group. This IL has shown to be a good extractant for some metals such as Cu(II) and Cd(II) [29], but it can also interact with Hg when incorporated in an electrode designed for the potentiometric determination of Cd(II) [30].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…In the study by Zhang et al [34] using the IL tricarpylylmethylammonium 2-(methylthio)benzoate, in which the S atom is bearing a methylene group instead of the H of TOMATS, it was reported that the extraction of Hg(II) occurred via an interaction of the metal with the S atom along with the contribution of the carboxylate group. In the case of TOMAS, it is reported in [30] that the extraction of Cd(II) is based on the chelating effect of the carboxylate group in addition to the formation of metal hydroxylates that forms a coordinate interaction between TOMAS and the metal ion.…”
Section: Pim With Tomats or Tomas: Extraction And Elution Experimentsmentioning
confidence: 99%
“…These techniques provide sensitive and accurate results at low concentration of analytes because of the complexity, high capital and operational costs, and time consumability of the systems [93]. On the other hand, they have several disadvantages, such as the requirement of expensive apparatus, complicated operation, high operation cost of operation and maintenance, and the requirement of well-controlled experimental conditions [94, 95].…”
Section: Applications Of Ionic Liquids As Sorbents Modifiersmentioning
confidence: 99%
“…Activated carbon, carbon nanotubes (CNT), and graphene are three of the most important carbon-based materials with a large specific surface area, and they provide high efficiency to extract various metal ions. Ismaiel et al [95] developed an IL-modified activated carbon as an electrode component. The IL-modified sorbent was prepared by mixing the measured palm shell-activated carbon (PSAC) powder and TOMAS.…”
Section: Applications Of Ionic Liquids As Sorbents Modifiersmentioning
confidence: 99%
“…The nut is usually collected after the removal of the mesocarp fiber, and the kernel inside the nut is separated from the nut's shell for subsequent oil extraction [8,9]. The shell can be utilized as fuel, used in the production of activated carbon for waste water treatment, and used in analytical applications [10][11][12]. The production of palm kernel starts with the cracking of palm nuts using a palm nutcracker to produce a cracked mixture of palm kernel and palm shell [13].…”
mentioning
confidence: 99%